2015
DOI: 10.1111/all.12695
|View full text |Cite
|
Sign up to set email alerts
|

Red meat allergic patients have a selective IgE response to the α-Gal glycan

Abstract: Galactose-α-1,3-galactose (α-Gal) is a mammalian carbohydrate with significance in a novel type of food allergy. Patients with IgE against α-Gal report severe allergic symptoms 3-6 h after consumption of red meat. We investigated whether IgE from red meat allergic patients recognizes other mammalian glycans than α-Gal or glycans from the plant kingdom and insects of importance in allergy. We found that none of the 24 red meat allergic patients investigated had an IgE antibody response against the other abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 165 publications
(215 reference statements)
1
26
0
Order By: Relevance
“…IgE recognition of BGG was completely abolished by α‐gal conjugated to BSA (Fig. 2) confirming that patients with delayed meat allergy selectively recognize α‐gal independently from the carrier protein 24.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…IgE recognition of BGG was completely abolished by α‐gal conjugated to BSA (Fig. 2) confirming that patients with delayed meat allergy selectively recognize α‐gal independently from the carrier protein 24.…”
Section: Discussionsupporting
confidence: 54%
“…Although IgE‐mediated, the symptoms occur atypically late for immediate hypersensitivity, namely 3–7 h after ingestion of red meat 23. The major allergen is not a protein but a mammalian oligosaccharide and removal of α‐gal dramatically reduces IgE binding to beef proteins 24. Several studies provided evidence that sensitization to α‐gal results from tick bites 11, 12, 25, 26.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As galactose-β1,4-N-acetylglucosamine is a part of the complex BTG glycan, we used direct ELISA to conclude that red meat-allergic patients’ IgE did not bind galactose-β1,4-N-acetylglucosamine itself and that there was a slight difference in IgE binding to α-Gal di- and trisaccharides. We have previously shown that red meat allergic patients have a selective IgE response to the α-Gal glycan that does not involve the protein backbone and, that Neu5Gc is not the target of the IgE response 36 . Plum and colleagues have shown that the IgE binding is localized to both galactose molecules but the the galactose-α1,3-galactose-β1,4-N-acetylglucosamine was not included in their study 37 .…”
Section: Discussionmentioning
confidence: 99%
“…BTG was chosen as a model α-Gal-containing protein and deglycosylated thyroglobulin was obtained using enzymatic deglycosylation 36 . Pepsin activity was verified according to manufacturer’s instructions prior to experiments.…”
Section: Methodsmentioning
confidence: 99%